THE EFFECT OF CORPORATE GOVERNANCE MECHANISM ON EARNINGS MANAGEMENT: THE COMPARATIVE STUDIES BETWEEN FIRMS LISTED ON SHARIA INDEX (JII-70) AND CONVENTIONAL INDEX (LQ-45) - Aditya Wisnu Candra Nugraha (Jurnal Ilmiah Mahasiswa FEB, 2020)
This research aimed to examine the effect of corporate governance mechanism on earnings management. The independent variables are board of commissioner size, board of commissioner meeting, board of commissioner independence, Board of competence, managerial ownership, and institutional ownership. In contrast, the dependent variable is earnings management. The sampling method was employed by purposive sampling. The research sample consisted of 305 companies in Indonesia. It contains 110 Sharia companies listed on JII-70 and 195 conventional companies listed on LQ-45 from 2015 until 2019. This research used multiple linear regression to examine the effect of independent variables on the dependent variable. The results show that board of commissioner size negatively affects earnings management, while the other corporate governance mechanism variables, which are board of commissioner meeting, board of independent commissioner size, board of commissioner competence, managerial ownership and institutional ownership have no effect on earnings management. In addition, the classification of company which measured by dummy variable is positive and significant, it means that the effect of corporate governance mechanism between companies listed on JII-70 and LQ-45 is different, and the effect is greater in companies listed on JII-70 than companies listed on LQ-45.Keywords: Corporate Governance Mechanism, Earnings Management.